2014
DOI: 10.1371/journal.pone.0090780
|View full text |Cite
|
Sign up to set email alerts
|

Lycium barbarum Polysaccharide Prevents Focal Cerebral Ischemic Injury by Inhibiting Neuronal Apoptosis in Mice

Abstract: Aims of the StudyTo investigate the neuroprotective effect of Lycium barbarum polysaccharide (LBP) on focal cerebral ischemic injury in mice and to explore its possible mechanism.Materials and MethodsMale ICR mice were used to make the model of middle cerebral artery occlusion (MCAO) after intragastric administration with LBP (10, 20 and 40 mg/kg) and Nimodipine (0.4 mg/kg) for seven successive days. After 24 h of reperfusion, neurological scores were estimated and infarct volumes were measured by 2, 3, 5-trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 31 publications
(30 reference statements)
3
40
0
1
Order By: Relevance
“…We examined the expression of AIF, BcL-2, Bax and Cyt-C in the hippocampus CA3 and cortex regions with immunofluorescence staining, and the expression of AIF, Cyt C, Bax and BcL-2 with western blot analysis. In conformity with other studies (Sun et al, 2011;Wang. et al, 2014), we found that AIF, Cyt C and Bax protein expressions were significantly greater compared with the sham-operated group 48 h after HI ( (Fig.9B, P<0.01) as well as a lower ratio of Bcl-2/Bax protein (Fig.9D, P<0.01) in the HI group compared with the sham group.…”
Section: Taurine Affects the Expression Of Apoptosis-related Proteinsupporting
confidence: 93%
“…We examined the expression of AIF, BcL-2, Bax and Cyt-C in the hippocampus CA3 and cortex regions with immunofluorescence staining, and the expression of AIF, Cyt C, Bax and BcL-2 with western blot analysis. In conformity with other studies (Sun et al, 2011;Wang. et al, 2014), we found that AIF, Cyt C and Bax protein expressions were significantly greater compared with the sham-operated group 48 h after HI ( (Fig.9B, P<0.01) as well as a lower ratio of Bcl-2/Bax protein (Fig.9D, P<0.01) in the HI group compared with the sham group.…”
Section: Taurine Affects the Expression Of Apoptosis-related Proteinsupporting
confidence: 93%
“…Coronal sections with the thickness of 2 mm were stained with 2% 2,3,5‐triphenyltetrazolium chloride (TTC) (Solarbio, China) for 30 min at 37°C followed by immersion in 4% paraformaldehyde solution overnight and photographed by a digital camera. Microscope image‐analysis software (Image‐Pro plus, USA) was used to calculate the infarct volumes as previously reported 20. Briefly, infarct area of each brain section was added to obtain the total infarct areas.…”
Section: Methodsmentioning
confidence: 99%
“…In diabetic condition. The dosage used in the present study was based on previous study and depended on our preparatory experiments [29,32].…”
Section: Animal Treatmentmentioning
confidence: 99%